pH Low Insertion Peptide-Modified Programmed Cell Death-Ligand 1 Potently Suppresses T-Cell Activation Under Acidic Condition - Sun, Ying; Hu, Linhan; Yang, Peng; Zhang, Min; Wang, Xinwei; Xiao, He; Qiao, Chunxia; Wang, Jing; Luo, Longlong; Feng, Jiannan; Zheng, Yuanqiang; Wang, Yi; et al. (Frontiers in Immunology, 2021)
Programmed cell death-ligand 1 (PD-L1)/PD-1 axis is critical for maintenance of immune homeostasis by limiting overactivation of effector T-cell responses. The impairment of PD-L1/PD-1 signals play an important role in the pathogenesis of inflammatory diseases, making this pathway an ideal target for novel therapeutics to induce immune tolerance. Given weakly acidic environment as a putative hallmark of inflammation, in this study we designed a new cargo by linking the ectodomain of murine PD-L1 to the N terminus of pHLIPs, a low pH-responding and membrane-insertion peptide, and demonstrated its potent immune-suppressive activity. Specifically, PD-L1-pHLIP spanned the cellular membrane and perfectly recognized its ligand PD-1 in acidic buffer. Immobile PD-L1-pHLIP actively inhibited T-cell proliferation and IFN-γ production. Importantly, soluble PD-L1-pHLIP retained its function to dampen T-cell responses under acidic condition instead of neutral aqueous solution. Overall, these data suggest that PD-L1-pHLIP has potentials to be a novel therapeutic avenue for T-cell-mediated inflammatory diseases.